Does Does Inflation and The Number of Taxpayers Affect Income Tax? - Fachrunnisa, Zidni Husnia; Luthfi, Rifna Ninda (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2023)
Income tax is the largest state revenue, and the COVID-19 pandemic impacted decreasing income tax in 2020. This study examines factors from outside the policy of the Directorate General of Taxes, such as inflation and factors from inside the Directorate General of Taxes, namely the number of taxpayers affecting income tax. This study uses secondary data from monthly realization data and income tax art. 25 targets during 2017-2020 at the Yogyakarta Tax Office (KPP Pratama Yogyakarta). The sample retrieval technique in this study uses a saturated sample method. Sample this study of 48 data. The data analysis technique used is multiple linear regression analysis. The results show that inflation does not affect income tax, while the number of taxpayers has a negative effect on income tax. From the results of this study, the greater the number of registered taxpayers, the lower the income tax revenue. Indonesia uses an internal self-assessment system to calculate taxes, and the taxes paid depend on a financial report sent to the tax office. So, corporate taxpayer compliance greatly determines the amount of income tax. This result implies that the government can optimise corporate taxpayer compliance through the Ministry of Finance or the general directorate of taxes. This study only uses income tax art. 25 deposited by corporate taxpayers.